2022
DOI: 10.3390/en15218299
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Integrated Electric Motor Drives: Opportunities and Challenges

Abstract: Integrated Motor Drives (IMDs) have recently received extensive attention. In electric vehicles (EVs), electric propulsion aircraft, and ship propulsion systems, integrated motors have the great potential to replace traditional motors with the distinct merits of compact size, high power density, high efficiency, and high-cost effectiveness. This paper investigates and reviews integrated motor drives’ development and critical technologies. It not only reveals the research progress of the motor structure, conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…Zhang et al found that motor power density has become a major concern in electric motor research, as shown in Figure 22. The application direction thus shifted to power systems for electric propulsion, fuel cell systems, robotic actuators and other small high-speed motors [6]. Heat dissipation and evacuation in the motor is still a challenge that needs to be improved urgently.…”
Section: Future Development Of High-speed Motor Coolingmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al found that motor power density has become a major concern in electric motor research, as shown in Figure 22. The application direction thus shifted to power systems for electric propulsion, fuel cell systems, robotic actuators and other small high-speed motors [6]. Heat dissipation and evacuation in the motor is still a challenge that needs to be improved urgently.…”
Section: Future Development Of High-speed Motor Coolingmentioning
confidence: 99%
“…Spindle thermal deformation caused by the error is often small, but the impact on the machining accuracy is prominent, and in serious cases, even causes damage to the spindle. Therefore, it is especially critical to provide efficient heat evacuation and address the thermal contortion of the motor spindle caused by temperature increase [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Integration of an IWM with an inverter can reduce long connecting wires and additional housing, resulting in increased power/torque density [74]. According to [75] the latest advancements of wide bandgap semiconductors has improved the power density and ability to withstand higher temperature for elongated time of power electronics modules.…”
Section: Integrated Power Electronics In Iwmsmentioning
confidence: 99%
“…Therefore, after the switch tube on the high side is opened for some time, the switch tube on the low side should be opened to charge the CBOOT. In this way, the logic of the control algorithm cannot make the high-side N-type switch tube open at 100% duty cycle [6] .…”
Section: Traditional High-side N-type Switch Tube Drive Schemementioning
confidence: 99%